Peranan Strategi Marketing Dalam Pengembangan Jaringan Bisnis Pada CV. Ciwidey Food - Resya Dwi Marselina; Salsabilla Puspa Rianty; Sawitri Nurhayati; Noval Robani Hardiansyah; Winda Aisyah (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This research was conducted to find out how the marketing strategy carried out by CV. Ciwidey food and what CV does. Ciwidey Food in developing its business network. Observation and interviews were the data collection techniques used in this study. The analysis method used is a descriptive qualitative analysis method, namely by collecting, processing and presenting data obtained when conducting research so that complete information is obtained about what is researched. Based on the results of the analysis that has been done, it can be concluded that the strategy in building a CV. Ciwidey Food can be done by expanding promotions through social media such as TikTok, Instagram, Facebook and WhatsApp. CV. Ciwidey Food builds a business network with expedition services in marketing its products. Expedition business networks can provide great benefits to CVs. Ciwidey Food by having a partnership with the network CV. Ciwidey Food can expand the distribution range of their products, such as being sent out of town and even abroad.